2015
DOI: 10.1088/0268-1242/30/9/094012
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of quaternary (GaIn)(AsBi) layers for optoelectronic terahertz detector applications

Abstract: GaIn)(AsBi) layers were grown on a GaAs substrate. Their alloy composition, structural characteristics as well as the optical and electrical parameters were determined. It was found that by incorporating Bi and In into the lattice of GaAs, the energy bandgaps can be as narrow as 0.6 eV. These epitaxial layers of quaternary bismide alloys have shorter than a one picosecond carrier lifetime and a relatively large dark resistivity, demonstrating that this material is a good candidate for ultrafast optoelectronics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Similar layers have been shown to produce THz radiation with a similar bandwidth when excited by longer wavelength sources, [ 76–78 ] including in the telecommunication C band. [ 79,80 ] In 2013, Heshmat et al benchmarked a GaAsBi‐based THz system against a commercially available LT–GaAs system and showed that it exhibited a larger bandwidth and a higher efficiency. [ 81 ] GaAsBi based PCAs are now commercially available.…”
Section: Recent Progress On Gaasbi Devicesmentioning
confidence: 99%
“…Similar layers have been shown to produce THz radiation with a similar bandwidth when excited by longer wavelength sources, [ 76–78 ] including in the telecommunication C band. [ 79,80 ] In 2013, Heshmat et al benchmarked a GaAsBi‐based THz system against a commercially available LT–GaAs system and showed that it exhibited a larger bandwidth and a higher efficiency. [ 81 ] GaAsBi based PCAs are now commercially available.…”
Section: Recent Progress On Gaasbi Devicesmentioning
confidence: 99%
“…The THz transient and its Fourier spectrum are measured when the emitter is biased at 10 V. Spectrum of the transient reaches frequencies larger than 3 THz, while its amplitude is comparable to that of THz transients obtained from LTG GaAs components under the same bias voltage. In 2015, the same group reported another photo-conductive THz detector fabricated by GaInAsBi on GaAs substrate [270]. Bismuth composition of GaInAs 1−x Bi x is characterized by XRD and EDX and reach unexpectedly high of about 10%.…”
Section: Photodetectorsmentioning
confidence: 99%
“…Similar layers have been shown to produce THz radiation with a similar bandwidth when excited by longer wavelength sources, [78][79][80] including in the telecommunication C band. [81,82] In 2013, Heshmat et al benchmarked a GaAsBi-based THz system against a commercially available LT-GaAs system and showed that it exhibited a larger bandwidth and a higher efficiency. [83] GaAsBi based PCAs are now commercially available.…”
Section: Thzmentioning
confidence: 99%